Nutrição no terço final da gestação: eficiência produtiva da vaca e desempenho da progênie até os doze meses de idade - Klein, John Lenon (2019)
The objective of this work was to evaluate the effects of nutritional levels in the final third of gestation on the productive performance of beef cows and progeny up to 12 months of age. Were used 83 Charolais x Nellore matrices, along with his progeny, with age ranging from 4 to 12 years, which were divided according to the nutritional level during the final third of gestation: natural pasture (PN); cows supplemented with 100% of energy and protein requirements (SP100); cows supplemented with 150% of energy and protein requirements (SP150). The experimental design was a completely randomized with three treatments and varied number of replications. SP100 and SP150 matrices presented better body condition at calving (2.92 and 2.95 vs 2.81 points) and at the beginning of the breeding season (2.90 and 2.95 vs 2.80 points) in relation to PN matrices. SP100 cows presented higher concentrations of cholesterol (182.29 mg/dL), as well as SP150 matrices obtained higher plasmatic concentrations of Albumin (3.23 g/dL) and Glucose (78.56 mg/dL) during lactation. Cows SP100 and SP150 obtained higher percentage of females with ovulatory follicles at 21 days postpartum in relation to PN matrices (45.68, 41.11 vs 11.00%, respectively). SP150 matrices presented higher pregnancy rate (40.74%), calves production (295.88 kg/cow) and consequently higher net sales revenue of the progeny. The progeny performance was influenced by the maternal nutritional level during gestation, where males offspring of SP100 and SP150 cows had a higher body weight at birth compared to those born to PN matrices (39.28, 39.13 vs 34.58 kg, respectively ), with similar postnatal performance among maternal nutritional levels during gestation. The birth weight of the daughters was not influenced by the nutritional levels of the cows during gestation (34.08 kg), however, SP100 and SP150 females presented better postnatal performance and consequently higher weight at twelve months of age compared to PN ( 300.71, 311.79 vs. 259.47 kg, respectively). SP150 females reached 60% of the adult weight earlier (345 vs 405 days) and presented higher percentage of suitable to reproduction at 12 months of age (84.08 vs 34.08%) compared to daughters of PN cows. Supplementation of the matrices with 100 or 150% of the requirements during final third of the gestation improves the productive efficiency of the beef cows, as well as the progeny performance up to 12 months of age.